From Cultural Violence to Positive Peace: Integrating Social Science and Islamic Reconciliation in Transforming Madurese Carok - Mohammad Takdir; Fadil; Basri (Penamas, 2026)
Carok—a machete duel fought in defence of honour within Madurese society—is a form of violence that is culturally sanctioned and underpinned by a hegemonic masculine code of honour. This study examines how the integration of behavioural science and Islamic reconciliation can transform carok into sustainable peace, by addressing the tension between a psychological interpretation of carok as a social behaviour believed to be a moral duty to uphold dignity, and reframing it through Galtung’s concept of cultural violence and Connell’s concept of hegemonic masculinity. Based on a qualitative approach—observation, in-depth interviews and documentation—and grounded in Amin Abdullah’s paradigm of integration and interconnection, this study brings together conflict transformation (Lederach), restorative justice (Zehr) and the principle of islah (sulh/reconciliation) in Islam. This analysis develops an integrated conflict resolution model comprising three dimensions: preventive (peace education, transformative da’wah, Islamic moral guidance), curative (religious mediation, psychological counselling, islah), and rehabilitative (a bio-psycho-social-spiritual approach to trauma recovery and social reintegration). This model reframes ‘carok’ from cultural violence into positive peace, whilst illustrating the potential for faith-based, interdisciplinary conflict transformation within Muslim communities with deeply rooted cultural traditions.